Effectiveness Of The Question Answer Method With Learning Media Variations For Improve The Achievement Of Ppkn In Sd Negeri 29 Teratak Panas - Eli Marnis (Fakultas Sastra Universitas Ekasakti, 2018)
To learn something well, we need to hear, see, ask questions about it, and discuss it with others. Not only that, teachers need to